ANALYZING OF STUDENTSSPEAKING SKILL THROUGH V-LOG - Anita Sitanggang (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
This study aimed to determine how students' speaking skills UHKBPNP English Education Study Program through vlogs on courses Interpersonal Speaking. This study uses a qualitative research design descriptive, where the writer describes and analyzes speaking ability. The population in the study was students of the UHKBPNP English Education Study Program in the first semester of the 2020/2021 Academic Year, totaling 10 people. Based on the results from the research it can be concluded that the students' speaking ability is between the "Above" level Average and Excellent. In other words, it can be supposed that vlog media can be attractive alternative media that can be used to improve the speaking skills of the college student.